Transformasi Makna Tari Gandrung; Studi Sosiologi Budaya melalui Perspektif Orientalisme Edward Said: The Transformation of the Meaning of Gandrung Dance: A Cultural Sociology Study through Edward Said's Orientalism Perspective - Clairine, Angela; Wiyono, Erica Natasha; Lestari, Eithar (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2024)
This research includes shifts in cultural values ​​due to the erosion of cultural identity due to developments over time. This research aims to provide in-depth knowledge to maintain cultural diversity and encourage greater appreciation of Indonesia's cultural heritage. The research method uses a qualitative method with an ethnographic approach to obtain in-depth data related to the transformation of the aesthetic aspects of the Gandrung Dance which changes its meaning over time. As a result of this research, it was found that there was a cultural transformation, especially the meaning of the Gandrung Dance, which was originally used as a ritual of thanks and gratitude from the Osing people to Dewi Sri, turning into a spectacle of entertainment for the wider community. Transformation of the meaning of Gandrung Dance, analyzing the interaction of culture and colonialism influencing changes in perceptions of Gandrung Dance. It can be found that even though Gandrung Dance has adapted to become entertainment, its traditional essence is still maintained through cultural preservation. Understanding the Gandrung dance through an orientalism perspective can provide insight into the dynamics of local culture and identity.